Trade-offs between vegetation and sediment availability in shaping long-term tidal network morphodynamics - Gu, Yuxian; Han, Guangxuan; Geng, Liang; Xie, Baohua; Zhang, Yanan; Xie, Danghan; Fagherazzi, Sergio; Zhang, Heyue; Coco, Giovanni; Zhou, Zeng (Frontiers in Marine Science, 2025)
IntroductionSaltmarsh introduction has been widely implemented to restore ecosystem services and promote sedimentation in tidal mudflats, yet its effects on tidal network dynamics remain hard to predict. The interplay between saltmarsh extent and sediment availability in shaping long-term mudflat morphodynamics is not fully understood.MethodsWe develop a two-dimensional biomorphodynamic model to examine the individual and combined influences of saltmarsh presence and sediment availability on the evolution of tidal-flat channels.Results and discussionOur results demonstrate that sediment availability controls the long-term morphological change of mudflats, while the presence of saltmarshes exerts substantial short-term alterations in mudflat evolution. During the initial phase of saltmarsh introduction, vegetation promotes the development of tidal networks, characterized by channel elongation, narrowing and deepening. However, under higher sediment supply, saltmarshes restrict sediment deposition on landward and central mudflats compared to that on unvegetated flats. Furthermore, sediment availability primarily facilitates the extension of pre-existing channels, while saltmarshes play a dual role in both generating new channels and elongating existing ones. This distinction highlights the competing mechanisms driving channel network development.